Development of Digital Teaching Materials through a Realistic Mathematics Approach used by Autograph Software to Improve Students' Problem-Solving and Mathematical Communication Abilities - Agus Selamat Telaumbanua; Waminton Rajagukguk; Hamidah Nasution (Jurnal Perspektif, 2026)
This study aims to determine: produce digital teaching materials through a Realistic Mathematics approach assisted by Autograph software that is valid, practical and effective; analyze the improvement of students' mathematical problem-solving abilities; and analyze the improvement of students' mathematical communication abilities after the implementation of the teaching materials. This study is a development research with a 4-D development model by Thiagarajan which includes the stages of define, design, develop, and disseminate. The results of the study indicate that: The digital teaching materials meet the criteria of valid, practical and effective; There is an increase in students' mathematical problem-solving abilities with an average N-Gain value of 0.77 which is included in the "High" category; There is an increase in students' mathematical communication abilities with an average N-Gain value of 0.62 which is included in the "Medium" category.